VD_FINDINFO HC / 2015 / 1008 vom 9. Oktober 2015 - VD Tribunal cantonal (2015)
BAIL À LOYER, RÉSILIATION, COMPARUTION PERSONNELLE | 261 al. 2 let. a CO, 271 al. 1 CO, 204 al. 3 CPC (CH), 68 al. 4 CPC (CH)